2016
DOI: 10.1182/blood-2015-08-666537
|View full text |Cite
|
Sign up to set email alerts
|

Sequential vs alternating administration of VMP and Rd in elderly patients with newly diagnosed MM

Abstract: Key Points• The sequential and alternating administration of VMP and Rd have equal efficacy and toxicity.• The greatest benefit of this total therapy approach was observed for patients aged 65 to 75 years.Bortezomib plus melphalan and prednisone (VMP) and lenalidomide plus low-dose dexamethasone (Rd) are 2 standards of care for elderly untreated multiple myeloma (MM) patients. We planned to use VMP and Rd for 18 cycles in a sequential or alternating scheme. Patients (233) with untreated MM, >65 years, were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 22 publications
0
40
0
1
Order By: Relevance
“…A Spanish group recently reported the preliminary results of a phase 3 study evaluating the efficacy of an alternating VMP/Len-Dex sequence in de novo MM patients. 57 This strategy demonstrated a high CR/sCR rate and an encouraging median progression-free survival of 28 months in high-risk MM patients. In this study, the outcome of standard-risk and high-risk patients did not differ significantly.…”
Section: Final Considerationsmentioning
confidence: 90%
“…A Spanish group recently reported the preliminary results of a phase 3 study evaluating the efficacy of an alternating VMP/Len-Dex sequence in de novo MM patients. 57 This strategy demonstrated a high CR/sCR rate and an encouraging median progression-free survival of 28 months in high-risk MM patients. In this study, the outcome of standard-risk and high-risk patients did not differ significantly.…”
Section: Final Considerationsmentioning
confidence: 90%
“…Apart from its established use as the conditioning agent of choice before ASCT, it has been studied in combination with IMiDs 45,9092 and PIs 46,93,94 both for induction of newly diagnosed myeloma and in the relapsed setting, the latter in combination with panobinostat. 95 It is reserved for patients who are not candidates for ASCT.…”
Section: Drugs Approved For Therapy For Multiple Myelomamentioning
confidence: 99%
“…This was the basis for the 18 cycles explored in the GEM10mas65 clinical trial (VMP+Ld combination), which yielded excellent clinical results. 12, 14 When we analyzed the molecular response in these elderly MM patients, we found that the proportion of patients achieving an MRD-negative status is significantly higher after 18 cycles of treatment (27% ( n =19) vs 11.5% ( n =8) after 18 and 9 cycles, respectively, P =0.04), confirming that a prolonged treatment improves the rate of molecular responses. Similar to the data obtained with other MRD methods, 7, 8, 15 the achievement of molecular responses measured by our NGS method is able to predict 3-year survival in patients enrolled in the GEM10 clinical trial.…”
mentioning
confidence: 68%
“…Patients were enrolled in the phase 2 trial for newly diagnosed elderly MM patients PETHEMA/GEM2010MAS65 study (www.clinicaltrials.gov as #NCT01237249); patients were randomized to receive 9 cycles of bortezomib/melphalan/prednisone (VMP) followed by 9 cycles of lenalidomide/dexamethasone (Rd; sequential arm, n =38) vs 18 alternating cycles of VMP/Rd (alternating arm, n =35). 12 Nighty-five percent ( n =69) of the patients experienced a CR according to the International Myeloma Working Group (IMWG). 13 Median follow-up of the series was 3 years.…”
mentioning
confidence: 99%